THE MOTIVATION OF LEARNING CLASS V STUDENTS OF SDN 005 SIKAKAK IN THE PROCESS OF LEARNING BLOOD IN THE PANDEMIC TIME COVID 19 - Sri Marlina; Islamuddin; Yogi Riantanam Isjoni (JURNAL RANDAI, 2021)
This research is motivated by the existence of an online learning process during the Covid 19 pandemic, so it is necessary to understand the learning process that can increase student learning motivation. In the online learning process there are many obstacles that cause the discussion process to be not very effective and efficient during the online learning process so that students' motivation in learning also decreases so that their learning achievement also decreases. This study aims to determine the level of student motivation in the online learning process during the Covid 19 pandemic. This type of research uses a quantitative approach using a survey method. The study was conducted on 50 students who took mathematics, engineering using a questionnaire. Data Analysis Techniques Using the Gutman scale. The results of the study A total of 4 students were classified as very low motivation to learn, as many as 6 students who belonged to low learning motivation, as many as 15 students who belonged to the medium learning motivation category, while as many as 25 students stated high motivation, while 0 students stated the motivation is very high. Recommendations need a learning process by giving group assignments by means of video calls